Program Projek Lingkar Sebagai Inovasi Penguatan Pendidikan Karakter di SD Negeri Tayem 01 - Hening, Banjar Mustika; Fajar, Wildan Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of the PROJEK LINGKAR (Character Network Program Integration of Mutual Cooperation Values, Active Reflective Collaboration) in developing the character of self-awareness, responsibility, and independence of fifth-grade students of SD Negeri Tayem 01. The study used a qualitative descriptive approach with 32 fifth-grade students, a class teacher, and parents selected purposively as subjects. Data were collected through observation, interviews, documentation, document studies, student reflection journals, and teacher reflection journals. Data validity was carried out using triangulation of sources and techniques, while data analysis followed the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the PROJEK LINGKAR Program was related to strengthening student character. Student participation in filling out reflection journals increased from 81% to 91%, while the courage to participate in story circle sessions increased from 25% to 41%. In addition, students showed developments in their ability to express feelings, carry out responsibilities, and learn more independently, accompanied by a decrease in conflict between students and an increase in mutual respect. These findings indicate that the PROJEK LINGKAR Program has the potential to support the strengthening of character education through collaborative and sustainable reflective activities